BENTUK PENYAJIAN TARI BETAJA PADA ADAT PERNIKAHAN SUKU DAYAK KANCIKNG DI KECAMATAN MELIAU KABUPATEN SANGGAU - Wilhilmina Tanema, Sesilia Wynni; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study analyzed the form of Betaja dance presentation in the community of dayak kancikng in Meliau, district Sanggau, which is based on the desire of researchers to make complete documentation about betaja dance. the problems in this study were, 1)what is the form presentation of the dayak betaja dance kancikng, 2)what is the betaja dance teaching material about art and culture lessons skills at the level of the class x senior high school. the purpose of this study was 1)describe the form of presentation of the betaja dance of the Dayak Kancikng tribe, 2)describe betaja teaching material for art and culture lessons and skills at class x senior high school. This research used descriptive method with qualitative research as well as used the choreographic approach. sources of data in this study and use choreographic approach. the data source in this study was Yohanes Aben male dancer male and musician, Tang S. Sos as a historian and male musician, Omba Latin dancer women. the data in this study were the results of interviews and observations in the form of notebooks, photographs and videos about Betaja dance in meliau, sanggau regency. data collection techniques using observation techniques, interviews and documentation. Keywords: Betaja District Form Kancikng Meliau Of Presentation.